Evaluating the Effects of a Twelve-Week Structured Exercise Program on Cognitive Performance and Brain Health in Older Adults - Rahayu, Dewi; Khatimah, Husnul; Mas’ud, Syarah (ScieClouds Publishing, 2024)
This study investigates the impact of a 12-week structured exercise program on cognitive function and brain health in older adults. A total of 100 participants aged 60 and above, with no severe cognitive impairment, were randomly assigned to an experimental group (n = 50) and a control group (n = 50). The experimental group participated in a program combining aerobic exercise, resistance training, and balance exercises, while the control group maintained their usual daily activities. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA) and Trail Making Test (TMT), and brain health was measured through blood-derived brain-derived neurotrophic factor (BDNF) levels and transcranial Doppler ultrasonography to evaluate cerebral blood flow. Pre-test and post-test data were analyzed using paired t-tests, independent samples t-tests, and ANCOVA to account for baseline differences. Results indicated significant improvements in cognitive performance, BDNF levels, and cerebral blood flow in the experimental group compared to the control group (p < 0.05). This study demonstrates that regular, structured exercise can effectively enhance cognitive function and brain health in older adults, addressing a significant gap in the literature regarding the role of multifaceted exercise programs in cognitive aging. These findings suggest that exercise may be a promising intervention to prevent cognitive decline and improve brain health in aging populations.